UNEARTHING THE PHILOSOPHICAL ROOTS OF PANCASILA ON DISTINCTIVE LEGAL TREATMENTS FOR CHILDREN IN CONFLICT WITH THE LAW - Bambang Santoso; Muhammad Rustamaji; Soehartono .Soehartono (Faculty of Law, Universitas Sebelas Maret, 2017)
Thus far, equality before the law is understood as an ideality without limitation and exception. Its enforceability is considered to apply indiscriminately for every law breaker. However, reality of law enforcement says differently when a perpetrator of the crime is called an early age child. Special regulations exist injustice system, law governing it as well as provisions derived from the children rights, although the child is positioned as dealing with the law. In such context of an establishment of law regarding children in conflict with the law, it is interesting to find philosophical roots of distinctive treatment negating equality before the law. The explorative step is more attractive, especially when many mosaics of conception has been discovered about what are the truths whena child is in conflict with the law: 1) violations committed by children are not purely mistakes of the children, 2) children are, nevertheless, having rights that must be fulfilled including when dealing with the law, 3) children has privileges with broad distribution of regulations in various sectors and according to the view based on Pancasila, they are keten (a link) of a nation. Such varied conceptions elicit necessity of unearthing philosophical roots, truths and realitiesthat are always plural. So that, the law established is not only be legal because it is formed in legitimate manner and by legitimate power (pedigree thesis), also incorporating theexisting basic values or moral principles, though not absolute, depending on condition of society (the moral thesis) (Twining, 2009). Thus, study of such legal products is not only be seen as the work of professional, but as Satjipto Rahardjo viewed, it is placed as an scientific object to explain that a law codified in legislation, though, is not something sacred to examine for its philosophical content.